2023
DOI: 10.3389/fgene.2022.1088230
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a tissue resident memory CD8 T cell-related risk score signature for colorectal cancer, the association with TME landscapes and therapeutic responses

Abstract: Backgrounds: The tissue resident memory CD8 T cell (Trm) constitutes an important component of the local immunity. In the context of malignant tumors, mounting evidence also supports the potential anti-tumor property of this cell subset. Therefore, identification of Trm marker genes and exploration of the causative effect of Trm in shaping tumor microenvironment (TME) heterogeneity might provide novel insights for the comprehensive management of cancer patients.Methods: By dissecting a single T cell transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Although risk stratification based on the SMLs can better predict the survival and clinical outcomes of patients with PAAD, it cannot distinguish populations with different TIME characteristics. Studies have shown that tumor subgroups derived from consensus clustering analysis have different TIME characteristics and impact immunotherapy response [ [66] , [67] , [68] ]. Accordingly, we performed a consensus clustering analysis based on the constructed SMLs, dividing the TCGA-PAAD cohort into two clusters to further explore the differences in clinical outcomes and the TIME of patients in different subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Although risk stratification based on the SMLs can better predict the survival and clinical outcomes of patients with PAAD, it cannot distinguish populations with different TIME characteristics. Studies have shown that tumor subgroups derived from consensus clustering analysis have different TIME characteristics and impact immunotherapy response [ [66] , [67] , [68] ]. Accordingly, we performed a consensus clustering analysis based on the constructed SMLs, dividing the TCGA-PAAD cohort into two clusters to further explore the differences in clinical outcomes and the TIME of patients in different subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…To comprehend the pathways and biological roles linked to the DEGs associated with CD8 + T cells, we conducted Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis using the “clusterprofiler” (version 4.8.1) package [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…The number of CD103+/CD8+ tumor-infiltrating lymphocytes (TILs) is a good prognostic and predictive factor for overall and relapse-free survival in patients with CRC [ 43 ]. Based on a combined analysis of single-cell and bulk RNA-sequencing data, the Trm-related gene risk score was closely correlated with the prognosis and treatment response in patients with CRC [ 52 ]. The percentage of resident memory CD103-expressing CD8+ and γδTCR+ intraepithelial lymphocytes was markedly reduced in the left and right colon of patients with familial adenomatous polyposis compared with healthy controls [ 53 ].…”
Section: Trm Cells and Gastrointestinal Cancersmentioning
confidence: 99%